3D-QSAR and Pharmacophore Identification of Benzothiazole Derivatives as Potent p56lck Inhibitors - Kanika Arora (Science Faculty of Chiang Mai University, 2019)
The current study aimed to identify the core structural features of selective p56lck inhibitors to design and develop molecules useful in inflammatory and autoimmune disorders. A set of known p56lck inhibitors were retrieved from the data bank using PHASE program and a three-dimensional pharmacophore hypothesis was constructed. Six point pharmacophore having four common structural features such as one hydrophobic site (H), two hydrogen bond acceptors (A), one hydrogen bond donor (D) and two aromatic rings (R) were developed. The best pharmacophore hypothesis was found to be AADHRR.15 which showed a regression coefficient value (r2) of 0.854 and produced a statistically significant 3 dimensional Quantitative structure activity relationship (QSAR) model. An external validation was further carried out to assess the quality and prediction reliability of the developed pharmacophore model. The generated model showed potential in good prediction of activity as indicated by the squared predictive correlation coefficient of 0.841 observed between experimental and predicted activity values of test set molecules. Thus, based on the results, it can be contemplated that the constructed hypothesis in this study seems to be a useful and reliable tool that can be used in identifying p56lck inhibitors with improved potency and efficacy.